2017
DOI: 10.1007/s12070-017-1103-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Use of High Resolution Computerized Tomography of Temporal Bone in Patients of Atticoantral Chronic Suppurative Otitis Media without Intracranial Complications Justified?

Abstract: Role of high resolution computerized tomography (HRCT) of temporal bone is established in cases of atticoantral chronic suppurative otitis media (CSOM) with intracranial complications. Routine use of HRCT in management of patients of atticoantral CSOM without intracranial complications has been an issue of debate. The aim of this study was to evaluate the routine use of HRCT of temporal bone in such cases. This study was a prospective study done at LG hospital, AMC MET Medical College, Ahmedabad to evaluate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
5
4
0
Order By: Relevance
“…In this study, male: female ratio was 1.14:1 which is in accordance with the study by Kemppainen et al 5 The most common presenting symptom was otorrhoea followed by hearing loss which is in accordance with a study by Yorgancilar et al 6 In our study, CT was 100% sensitive for diagnosing cholesteatoma by HRCT images which is in correlation with the studies by Sirigiri et al and Bathla et al 7,8 It was 100% specific for diagnosing cholesteatoma in epitympanum, mesotympanum and hypotympanum but was less specific for cholesteatoma in antrum and aditus. In our study, HRCT was found to have less sensitivity in differentiating cholesteatoma from granulations which is in consonance with other studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, male: female ratio was 1.14:1 which is in accordance with the study by Kemppainen et al 5 The most common presenting symptom was otorrhoea followed by hearing loss which is in accordance with a study by Yorgancilar et al 6 In our study, CT was 100% sensitive for diagnosing cholesteatoma by HRCT images which is in correlation with the studies by Sirigiri et al and Bathla et al 7,8 It was 100% specific for diagnosing cholesteatoma in epitympanum, mesotympanum and hypotympanum but was less specific for cholesteatoma in antrum and aditus. In our study, HRCT was found to have less sensitivity in differentiating cholesteatoma from granulations which is in consonance with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, HRCT was found to have less sensitivity in differentiating cholesteatoma from granulations which is in consonance with other studies. [8][9][10][11] HRCT was found to be helpful in correctly picking out extent of the disease which is in agreement with studies by Donoghue et al and Mafee et al 12,13 Early radiological sign of cholesteatoma is bone erosion. In our study, all cases (90%) reported in CT were confirmed at surgery.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[ 15 ] Even one of the studies has revealed a specific sign (mass effect sign) for diagnosing cholesteatoma on HRCT. [ 16 ] Thus, similar to our study many papers have documented that HRCT scan findings correlate well with surgical findings for cholesteatoma and bony erosions,[ 14 15 16 17 18 19 20 21 22 23 ] however, few studies have disputed the above findings. [ 24 25 ] This may be due to the difference in the technical parameters used for the HRCT acquisition in different studies as well as the varying expertise of the radiologists involved in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…In a recent study, the routine use of HRCT temporal bone has been justified even in patients without intracranial complications. [ 14 ] In another study done on the pediatric population, the authors have revealed that the preoperative HRCT temporal bone scan is a useful technique for the evaluation of the cholesteatoma surgery owing to a very good correlation between imaging and intraoperative findings. [ 15 ] Even one of the studies has revealed a specific sign (mass effect sign) for diagnosing cholesteatoma on HRCT.…”
Section: Discussionmentioning
confidence: 99%